Interest in Babies Negatively Predicts Testosterone Responses to Sexual Visual Stimuli Among Heterosexual Young Men. (January 2016) - Zilioli, Samuele; Ponzi, Davide; Henry, Andrea; Kubicki, Konrad; Nickels, Nora; Wilson, M. Claire; Maestripieri, Dario
Men's testosterone may be an important physiological mechanism mediating motivational and behavioral aspects of the mating/parenting trade-off not only over time but also in terms of stable differences between mating-oriented and parenting-oriented individuals. In this study, we tested the hypothesis that self-reported interest in babies is inversely related to testosterone reactivity to cues of short-term mating among heterosexual young men. Among 100 participants, interest in babies was related to a slow life-history strategy, as assessed by the Mini-K questionnaire, and negatively related to testosterone responses to an erotic video. Interest in babies was not associated with baseline testosterone levels or with testosterone reactivity to nonsexual social stimuli. These results provide the first evidence that differential testosterone reactivity to sexual stimuli may be an important aspect of individual differences in life-history strategies among human males.